(untitled) (Global Journal of Medical Research, 2019)
The radicular cyst is one of the most commonly occurring cysts in the oral cavity. It is usually preceded by trauma or an infection which is followed by enlargement. In recent times there are several treatment procedures that are being applied to improve the postoperative condition and to accelerate the process of healing and regeneration in the affected site. A 30year-old patient reported to our OPD with the chief complaint of swelling on the left side of the face since 2-3 months, on investigation a diagnosis of radicular cyst was given, which was initially treated by endodontic treatment of the involved tooth followed by enucleation of the cyst and apicoectomy. PRF and G bone graft-hydroxyapatite crystals were placed for aesthetic rehabilitation with 21.